The secret crusade - Doherty, Gordon, 1978- (Assassin's creed ;, 2011)
"Altair embarks on a formidable mission - one that takes him throughout the Holy Land and shows him the true meaning of the Assassin's Creed. To demonstrate his commitment, Altair must defeat nine deadly enemies, including Templar leader, Robert de Sable. Altair's life story is told here for the first time: a journey that will change the course of history; his ongoing battle with the Templar conspiracy; a family life that is as tragic as it is shocking; and, the ultimate betrayal of an old friend"